Changes in radiocarpal and intercarpal arthrodesis incidence in Sweden: A 16-year retrospective analysis of 5 189 surgeries. - Michael Axenhus; Elsa Pihl; Cecilia Mellstrand Navarro; Viktor Schmidt (PLoS ONE)
Radiocarpal and intercarpal arthrodesis are common procedures for managing advanced arthritis, post-traumatic conditions, and failed interventions. This observational study analysed 5,189 cases of arthrodesis registered in the Swedish National Patient Register between 2008 and 2023 to identify surgical trends and future projections. Of these, 2,434 were radiocarpal and 2,755 intercarpal arthrodesis. Arthrodesis of the radiocarpal and intercarpal joints demonstrate fluctuating trends, regional disparities, and relatively equal rates between men and women. Younger men more often undergo intercarpal arthrodesis, while older women are in majority regarding radiocarpal arthrodesis, potentially reflecting differences in disease presentation, surgical indications, or occupational factors. A slight overall decline in arthrodesis rates suggests a shift towards alternative treatments like denervation or arthroplasty. These findings highlight the need for continued adaptation to evolving surgical techniques and standardised national care programs to optimize patient care and outcomes and mitigate inequalities in health care.